Transport mechanisms as indicators of the durability of precast recycled concrete. (1st February 2021) - Fiol, F.; Thomas, C.; Manso, J.M.; López, I.
Highlights: Analysis review of using recycled concrete aggregates from precast concrete. Physical and mechanical properties of SCC using RCA were analyzed. Relationships between SCC properties have been discussed. The microstructure of SCC using RCA was analyzed. Recommendations for further investigations on RAC with precast wastes. Abstract: The objective of this paper was to analyze the influence of crushed precast concrete waste on the transport mechanisms as indicators of the durability of precast recycled self-compacting concrete (SCC) as an alternative to the coarse fraction of natural aggregate. The replacement percentages were 20%, 50% and 100%, by weight, of the silica gravel 2/12.5 mm. Two types of SCC were manufactured: the first with a minimum compressive strength of 30 MPa (HR-30) and the second with a minimum strength of 45 MPa (HR-45). The recycled SCC's mechanical characteristics such as compressive strength, splitting tensile strength, flexural strength and modulus of elasticity were analyzed. Regarding the physical properties related to transport mechanisms, the influence of the recycled aggregate on the porosity, absorption, penetration of water under pressure, density of hardened concrete and ultrasonic pulse velocity was analyzed. All these properties were compared with those of a control concrete. The results of the mechanical tests provide values close to those obtained for the control SCC, while, in terms of durability the results fulfil the limit values that are considered for a good quality concrete. Therefore, it can be concluded that the use of crushed precast concrete waste with different degrees of substitution is a viable alternative in the manufacture of more sustainable SCC.